2019
DOI: 10.13189/ujer.2019.070512
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Shared Leadership and Positive Psychological Capitals of Teachers at Primary and Secondary Schools

Abstract: The purpose of this study was to measure shared leadership and positive psychological capital levels of teachers at schools and to examine the relationship between these two variables. Descriptive survey and relational research models were used in the study. The sample group of the study was comprised of 550 teachers working at primary and secondary schools at the Battalgazi and Yeşilyurt central districts of the province of Turkey during the 2017-2018 academic year. The data were acquired via Shared Leadershi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
3
0
1
Order By: Relevance
“…According to the teachers' opinions, the research findings show a significant and positive relationship between the dimensions of effective school and positive psychological capital. This result coincides with the results of Çobanoğlu and Bozbayındır's (2019) study in which they determined the leadership characteristics and positive psychological capital levels of administrators and examined the relationship between these two variables. They found a significant relationship between positive psychological capital and shared leadership characteristics of primary and secondary school teachers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…According to the teachers' opinions, the research findings show a significant and positive relationship between the dimensions of effective school and positive psychological capital. This result coincides with the results of Çobanoğlu and Bozbayındır's (2019) study in which they determined the leadership characteristics and positive psychological capital levels of administrators and examined the relationship between these two variables. They found a significant relationship between positive psychological capital and shared leadership characteristics of primary and secondary school teachers.…”
Section: Discussionsupporting
confidence: 87%
“…According to the findings of the study, transformational leadership style significantly predicts positive psychological capital of teachers. According to the results of the research conducted by Çobanoğlu and Bozbayındır (2019) regarding the manager dimension, which is an important dimension of an effective school, it was seen that there is a significant relationship between the leadership styles of effective school managers and their teachers. According to the findings obtained from Çiftçi's (2019) study; there is a statistically significant relationship between the positive psychological capital scale and the sub-dimensions of self-efficacy, optimism, confidence, extraversion, resilience and hope.…”
Section: School Effectivenessmentioning
confidence: 99%
“…Some studies on all levels of school in Turkey (Korkmaz, 2011;Uslu & Beycioglu, 2013) found out that shared leadership was at a "high" level, while a study in primary schools (primary and secondary schools) was at a "mostly shared" level (Yilmaz, 2013). Similar to these studies, there are many studies that state that the level of shared leadership is "mostly shared" (Saricice ; 2014) and "high" (Ba ir Cobanoglu, 2019). Based on the results of these studies in the field, it can be stated that the shared leadership in schools in Turkey is at a high level with respect to to the teachers' opinions.…”
Section: Discussionmentioning
confidence: 80%
“…In the quantitative findings of this research, which was carried out in a mixed design, it was determined that the shared leadership behaviors of school principals were at a low level according to teacher perceptions. Contrarily, it was determined that principals of schools demonstrated shared leadership behaviors at a high level according to teachers' perceptions in a lot of studies (Bakır and Aslan, 2014;Çobanoglu and Bozbayındır, 2019;Korkmaz and Gündüz, 2011;Uslu and Beycioğlu, 2013;Torres, Bulkley and Kim, 2020). After seeing that the results of the current quantitative study were clearly different from other studies in the literature, it was decided to investigate the reasons for this situation.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 82%